Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12879-021-06891-1
|View full text |Cite
|
Sign up to set email alerts
|

Serotype distribution and incidence of invasive early onset and late onset group B streptococcal disease amongst infants in Singapore

Abstract: Background The current group B streptococcal (GBS) preventive measures had reduced invasive GBS early onset disease (EOD) incidences worldwide, but the late onset disease (LOD) incidences had remained unchanged. Administration of a safe and effective GBS vaccine in addition to the current strategies were thought to be the next steps in reducing the incidences of invasive GBS infection especially LOD. In this study, we aimed to examine the causative GBS serotypes in invasive GBS disease, determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Furthermore, our study found extremely few cases of invasive GBS disease in children aged ≥1 year. Focusing on the bacterial profile, the most common serotype in this study was serotype III, which was the same as that reported in other domestic studies and studies conducted in other countries [9,16,20,21]. Furthermore, the proportion of ST17, recognised as a hypervirulent international clone associated with invasive neonatal disease, was as high as 29.7% in 19 of the 64 patients aged <1 year in whom ST could be identified.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, our study found extremely few cases of invasive GBS disease in children aged ≥1 year. Focusing on the bacterial profile, the most common serotype in this study was serotype III, which was the same as that reported in other domestic studies and studies conducted in other countries [9,16,20,21]. Furthermore, the proportion of ST17, recognised as a hypervirulent international clone associated with invasive neonatal disease, was as high as 29.7% in 19 of the 64 patients aged <1 year in whom ST could be identified.…”
Section: Discussionsupporting
confidence: 83%
“…To date, ten GBS capsular serotypes have been identified (Ia, Ib, II-IX), but six serotypes (Ia, Ib, II-V) are responsible for 98% of GBS colonization and 99% of all EOD and LOD worldwide [ 3 , 4 ]. Moreover, studies have shown that serotype III is more commonly associated with LOD (73.0–80%) than EOD (42.9–47.0%), while other serotypes including Ia, Ib, and V are more frequently isolated in EOD than in LOD ( Table 1 ) [ 7 , 19 ].…”
Section: Serotype Distributionmentioning
confidence: 99%